The Crisis in Music Education Resulting from the Demise of Educational Institutions - Angel-Alvarado, Rolando (Universidad de Costa Rica, 2019)
Educational institutions currently face a crisis due to various factors that cast doubt on essential principles of equity and quality. This study reviews value chains in educational institutions, ranging from supranational agencies to schools, based on a music education perspective. The methodology has a qualitative design, with a Grounded Theory approach centered on a Constant Comparative Method. Results show that the decline of educational institutions is replicated in music education and furthermore, what is of greatest concern, is that socio-educational inequality emerges from the curriculum design phase. To conclude, a sociomusical approach is one way of overcoming this crisis since it recognizes the world´s cultural complexities by promoting systematic interaction between educational institutions and other social groups throughout the world.